2023
DOI: 10.22270/jddt.v13i1.5819
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acute, subacute toxicity and in vivo impact of aqueous decoction of Flemingia faginea Guill. & Perr. (Barker) leafy stems on NMRI mice and normotensive Wistar rats

Abstract: Introduction: Flemingia faginea, a Fabaceae family medicinal plant, has been used for a long time in Burkina Faso for the treatment of hypertension and excess salt. However, the safety of the preparations derived from this plant has not yet been scientifically documented. This study aimed to evaluate the acute and subacute oral toxicity of the leafy stems aqueous decoction of F. faginea (FAD) in healthy normotensive mice and rats and the impact on their normal blood pressure. Material and Methods: The acute or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The results showed that HE_SOS (2000 mg/kg bw) and HE_ROS (2000 mg/kg bw) did not cause any mortality or visible behavioral changes in female NMRI mice. The LD50 of HE_SOS and HE_ROS is estimated at 5000 mg/kg bw according to the United Nations Globally Harmonised System with demonstrated adverse effects [22,31]. These results show that extracts from the stems and roots of Odontonema strictum can be used safely.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The results showed that HE_SOS (2000 mg/kg bw) and HE_ROS (2000 mg/kg bw) did not cause any mortality or visible behavioral changes in female NMRI mice. The LD50 of HE_SOS and HE_ROS is estimated at 5000 mg/kg bw according to the United Nations Globally Harmonised System with demonstrated adverse effects [22,31]. These results show that extracts from the stems and roots of Odontonema strictum can be used safely.…”
Section: Discussionmentioning
confidence: 85%
“…The acute oral toxicity test for HE_ROS and HE_SOS was performed on female mice following OECD guideline 423 [21,22]. Two (02) batches, each consisting of three mice, were placed separately in polypropylene cages: a test batch of three mice and a control batch of three mice.…”
Section: Acute Oral Toxicitymentioning
confidence: 99%
“…For this reason, HE_FDM and AM_FDM were evaluated for acute oral toxicity. The results showed that their LD50 is estimated at 5000 mg/kg bw according to the United Nations Globally Harmonised System with demonstrated adverse effects" [17]. "These results show that the immature fruits of the plant are practically non-toxic and can therefore be used appropriately.…”
Section: Discussionmentioning
confidence: 97%
“…"The acute oral toxicity test for HE_FDM and AM_FDM was performed on female NMRI (Naval Medicinal Research Institute) mice by OECD guideline 423" [4,17]. Two batches, each consisting of three mice, were made up and placed separately in polypropylene cages, a control batch of 03 mice and a test batch of 03 mice.…”
Section: Acute Oral Toxicitymentioning
confidence: 99%
“…The acute oral toxicity test for aqueous extract of Diospyros mespiliformis leaves was performed on female NMRI (Naval Medicinal Research Institute) mice in accordance with OECD guideline 423 [15] [16]. Two (02) batches, each consisting of three mice, were made up and placed separately in polypropylene cages: a control batch of three mice and a test batch of three mice.…”
Section: Acute Oral Toxicitymentioning
confidence: 99%